Evaluation of Management Training Athletic Sports Club of Run, Jump and Floor in Sport and Youth Office (Diaspora) Aceh - Zikrur Rahmat; Irfandi Irfandi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The purpose of this study was to evaluate the management of Athletic sports club training, especially the numbers for the run, jump and throw of the Aceh Dispora, and specifically aimed at assessing the extent of the development of existing Athletic sports clubs in each District / City under the guidance of the Aceh Dispora, in the study this research is Sabang, Aceh Besar, Pidie Jaya, Bener Meriah, Gayo Lues, Aceh Jaya, Simeulue and Aceh Singkil. The method used is a qualitative research method, which only assesses the feasibility of developing the management of Athletic sports clubs. The results obtained showed that: 1) facilitating the management / management of athletic sports, especially the numbers of running, jumping and throwing the Aceh Dispora Patronage in each Regency / City, 2) creating a management evaluation plan for Athletic sports club training, especially running numbers, lompat dan lempar Binas Dispora in Aceh Province, including all Dispora in each District / City that overshadow Athletic sports activities, 3) make monthly, weekly and daily training programs, 4) apply rules to be more disciplined, directed and motivated in practice, 5) can organize well about scheduling, determine the place of training especially the existing Dispora Aceh Athletic Sports Club in each Regency / City. The results of the research and discussion show that the process of managing athletes in Aceh Athletic Sports clubs in the regions is still relatively low, this is because the management, management, recruitment and financing processes are still classified as less / still in the process of improving towards more advanced.